Kolektyw edukacyjny 2.0. Między inspiracjami lekturą prac Makarenki a Latourem - Maksymilian Chutorański (Problemy Wczesnej Edukacji)
The text is devoted to the question of the contemporary relevance of – central to the Makarenko’s pedagogy – the category of the collective. Confronting its understanding as developed by the Soviet pedagogue with researchers referring to the so-called “flat ontology”, I develop a thesis that makes it possible to cross the dualistic way of thinking about culture and nature. Consequently, it allows then question concerning the “extended” non(only)human educational community to be posed.